Pengembangan Media Berbasis Power Point Interaktif Pada Materi Manajemen Waktu - Hidayani, Dwi Nurul; Venty, Venty; Widiharto, Chr. Argo (Universitas Nusantara PGRI Kediri, 2024)
Guidance and counseling teacher face challenges in preparing service materials, thus necessitating the development of media that are easy for them to operate. One strategy to enhance the effectiveness of the learning process is through the use of interactive media, such as PowerPoint. This application is highly effective for presenting materials because it can integrate text, images, colors, layouts, and animations tailored to students' needs. The purpose of this study is to develop valid and reliable media to support teachers in delivering content in accordance with needs analysis results. This research employs a research and development (R&D) method following the ADDIE model, which includes five phases: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data were collected through feasibility tests by media experts and practicality tests involving teachers in a limited trial. The validity test by media experts showed a result of 75%, while the practicality trial by six teachers showed an effectiveness of 91.6%. Based on these results, the developed media has proven to be highly effective and suitable for use in schools.